Strategic Planning in the Performance Accountability System of Government Agencies - Rahmah Maulani Oktaviyanti; Ismanudin (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The effectiveness of administering government affairs is largely determined by the quality of public services by the government agency concerned. The government sector continuously needs to carry out strategic planning, and evaluate itself and improve performance on an ongoing basis so that government goals according to their main tasks and functions and authority can be achieved effectively, efficiently and accountably. In order to create a clean and good government, synergy between three basic elements is needed, namely participation, transparency and accountability. The element of accountability has been outlined in Presidential Instruction No. 7 of 1999 concerning Accountability for the Performance of Government Agencies (AKIP), which essentially requires every government agency as an element of state government administration to be responsible for the implementation of its main tasks and functions, as well as resource management authority based on strategic planning determined by each agency. The accountability in question is in the form of a report submitted to each superior, supervisory institutions and accountability assessors, and finally submitted to the President as Head of Government. The report describes the performance of the government agencies concerned through the Government Agencies Performance Accountability System (SAKIP). It is hoped that this article can add to the repertoire and understanding of related concepts at theoretical and practical levels.